Revitalization of Supervision of the Judicial Commission as Strengthening Judicial Institutions in Maintaining the Independence and Integrity of Judges - Zamroni Faizal Abdi; Chintya Khaerunnisa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
External supervision of judges' performance is done by the Judicial Commission (JC), namely by providing input regarding the mechanism for providing sanctions for violations of the code of ethics committed by judges. The task of the Judicial Commission regarding recommendations for sanctions for violations committed by judges involves collaborating with the Supreme Court because the judicial commission does not have the right to impose sanctions directly on judges. Therefore, efforts are urgently needed to improve the integrity of judges as law enforcers from the Judicial Commission institution that has the authority to act as an external monitor of the behavior of judges. The Judicial Commission also guarantees that they can maintain and increase the independence and integrity of judges. Regarding the supervision of the Judicial Commission as a strengthening of the Judiciary institution in maintaining the independence and integrity of judges, this research is conducted using normative methods. The data collection techniques are done by searching documents and scientific books to determine the theoretical basis in the form of positive legal material appropriate to the research object.